Performance Intelligence of Sustainable Waste Management through SWOT Analysis at the 3R Waste Management Site in Subang Antapani, Bandung - Rohman, Kukuh Padli; Warlina, Lina; Diva Awatara, I Gusti Putu (Universitas Lampung, 2024)
The city government, in its efforts to reduce waste being thrown into landfills, has attempted to build several 3R TPSs. On the other hand, 3R is still found not to be implemented optimally and there is still the practice of collecting, transporting, throwing away. From the research conducted, the status of TPS 3R Subang is rated in the poor category. For this reason, intelligence is needed to improve performance to the adequate category or the good category. The aim of this research is to intelligence of improving the performance of TPS 3R Subang from low to medium or good. The analytical method used is a qualitative method with SWOT analysis. SWOT has two internal and external factors and it is necessary to identify internal and external factors from TPS 3R Subang. The results of carrying out this intelligence obtained coordinates (0.6; 0.2), namely in quadrant I (SO), meaning that what shall be done to improve performance is to use strength to be able to seize every opportunity, namely optimizing the use of incinerator machines, optimizing terawang stone compost, maggot cultivation, and seize opportunities by selling cultivated in larger volumesWaste Management; Intelegence; SWOT; TPS 3R